Distribution Characteristics of Soil Viruses Under Different Precipitation Gradients on the Qinghai-Tibet Plateau - Cao, Miao-Miao; Liu, Si-Yi; Bi, Li; Chen, Shu-Jun; Wu, Hua-Yong; Ge, Yuan; Han, Bing; Zhang, Li-Mei; He, Ji-Zheng; Han, Li-Li (Frontiers in Microbiology, 2022)
Viruses are extremely abundant in soil environment, and have potential roles in impacting on microbial population, evolution and nutrient biogeochemical cycles. However, how environment and climate changes affect soil viruses is still poorly understood. Here, a metagenomic approach was used to investigate the distribution, diversity and potential biogeochemical impacts of DNA viruses in 12 grassland soils under three precipitation gradients on the Qinghai-Tibet Plateau which is one of the most sensitive areas to climate change. A total of 557 viral operational taxonomic units (vOTUs) were obtained spanning 152 viral families from the 30 metagenomes. Both Virus-like-particles (VLPs) and microbial abundance increased with average annual precipitation. A significant positive correlation of VLPs counts was observed with soil water content (SWC), total carbon (TC), total nitrogen (TN), soil organic matter (SOM) and total phosphorus (TP). Among these biological and abiotic factors, SWC mainly contributed to the variability in VLPs abundance. The order Caudovirales (70.1% of identified viral order) was the predominant viral type in soils from the Qinghai-Tibet Plateau, with Siphoviridae family being the most abundant. Remarkably, abundant auxiliary carbohydrate-active enzyme (CAZyme) genes represented by glycoside hydrolases were identified, indicating that soil viruses may play a potential role in carbon cycle on the Qinghai-Tibet Plateau. There were more diverse hosts and abundant CAZyme genes in soil with moderate precipitation. Our study provides strong evidence that changes in precipitation impact not only viral abundance and virus-host interactions in soil but also viral functional potential, especially carbon cycling.